Harmful effect of beer on bovine enamel microhardness - In vitro study - Zanatta, Rayssa Ferreira [UNESP]; Esper, Maria Ângela Lacerda Rangel [UNESP]; Valera, Marcia Carneiro [UNESP]; Melo, Renata Marques [UNESP]; Bresciani, Eduardo [UNESP] (Public Library of Science (PLoS), 2016)
This study aimed to evaluate the effect of beers on the bovine enamel microhardness. Fifty rectangular (1 × 3 × 1 mm-height × width × thickness) enamel specimens were obtained from permanent bovine incisors, and divided into five groups (n = 10) according to the treatment employed: Saliva, Coke, Brahma, Heineken, and Budweiser. Microhardness (Knoop) were obtained before; after 5, 30 and 60 min of immersion in each solution. The data were analyzed using repeated two-way ANOVA and Tukeýs test (p<0.05). Coke decreased the microhardness in all immersion times, and Heineken, showed low values after 60 minutes. Beers tested have low potential to cause enamel erosion when compared to Coke.